Mouse JMJD4 is dispensable for embryogenesis. Issue 7 (16th May 2016) - Yoo, Hyunjin; Son, Dabin; Lee, Young Jae; Hong, Kwonho
SUMMARY: Jumonji C domain‐containing demethylase 4 (JMJD4) is thought to help regulate mRNA translation, yet its precise in vivo role during mouse development has not been addressed. In the present study, we examined the contribution of this demethylase to embryonic stem cell (ESC) differentiation, and established a Jmjd4 ‐knockout mouse to explore its role during embryonic development. Jmjd4 expression is diminished upon ESC differentiation, and becomes restricted to certain developing organs, such as the eyes and gut, in embryonic Day‐11.5 embryos. Unexpectedly, Jmjd4 ‐null ESCs exhibited normal colony morphology and maintained normal expression of pluripotent genes. Furthermore, Jmjd4 ‐knockout embryos are born at a normal Mendelian ratio. Thus, JMJD4 is dispensable in murine development. Mol. Reprod. Dev. 83: 588–593, 2016. © 2016 Wiley Periodicals, Inc .